Lipid lowering agents are associated with a slower cognitive decline in Alzheimer's disease. Issue 12 (16th November 2005) - Masse, I; Bordet, R; Deplanque, D; Al Khedr, A; Richard, F; Libersa, C; Pasquier, F
Abstract : Background: Data from epidemiological studies and animal models imply that disturbances in cholesterol metabolism are linked to Alzheimer's disease susceptibility. Lipid lowering agents (LLAs) may have implications for the prevention of Alzheimer's disease. Objective: To investigate whether LLAs are associated with a slower cognitive decline in Alzheimer's disease. Methods: An observational study in 342 Alzheimer patients followed in a memory clinic for 34.8 months (mean age 73.5 years, mini-mental state examination score (MMSE) 21.3 at entry); 129 were dyslipaemic treated with LLAs (47% with statins), 105 were untreated dyslipaemic, and 108 were normolipaemic. The rate of cognitive decline was calculated as the difference between the first and last MMSE score, divided by the time between the measurements, expressed by year. Patients were divided into slow and fast decliners according to their annual rate of decline (lower or higher than the median annual rate of decline in the total population). Results: Patients treated with LLAs had a slower decline on the MMSE (1.5 point/year, p = 0.0102) than patients with untreated dyslipaemia (2.4 points/year), or normolipaemic patients (2.6 points/year). Patients with a slower decline were more likely to be treated with LLAs. Logistic regression analysis, with low annual cognitive decline as the dependent variable, showed that the independent variable LLA (treated with or not) was positively associated with the probability of lower cognitive decline (odds ratio = 0.45, p = 0.002). Conclusions: LLAs may slow cognitive decline in Alzheimer's disease and have a neuroprotective effect. This should be confirmed by placebo controlled randomised trials in patients with Alzheimer's disease and no dyslipaemia.